2000
DOI: 10.1046/j.1432-1327.2000.01609.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the gene and processed pseudogenes encoding the human and rabbit translationally controlled tumour protein (TCTP)

Abstract: In humans and rabbits, the TPT1 gene encoding the translationally controlled tumour protein TCTP generates two mRNAs (TCTP mRNA1 and TCTP mRNA2) which differ in the length of their 3 H untranslated regions. The distribution of these mRNAs was investigated in 10 rabbit and 50 human tissues. They were transcribed in all tissues investigated, but differed considerably in their quantity and ratio of expression. This indicates an extensive transcriptional control and involvement of tissue-specific factors. In the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
91
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 44 publications
4
91
0
Order By: Relevance
“…The yeast orthologue of TCTP was named 'microtubule and mitochondria interacting protein' (Mmi1p) (Rinnerthaler et al 2006), but in another paper, it was also identified as the 'translation-machinery-associated protein 19' (TMA19) (Fleischer et al 2006), and yet the gene symbol in yeast is YKL056c. In contrast, the gene symbol in higher eukaryotes is TPT1, for 'tumour protein, translationally controlled-1' (Thiele et al 2000).…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
See 4 more Smart Citations
“…The yeast orthologue of TCTP was named 'microtubule and mitochondria interacting protein' (Mmi1p) (Rinnerthaler et al 2006), but in another paper, it was also identified as the 'translation-machinery-associated protein 19' (TMA19) (Fleischer et al 2006), and yet the gene symbol in yeast is YKL056c. In contrast, the gene symbol in higher eukaryotes is TPT1, for 'tumour protein, translationally controlled-1' (Thiele et al 2000).…”
Section: The 'Translationally Controlled Tumour Protein Tctp': Names mentioning
confidence: 99%
“…Several of these pseudogenes have been studied in some detail in the rabbit (Thiele et al 2000) and in mouse (Fiucci et al 2003), and only few were found to have the potential to produce a protein product.…”
Section: Gene Structure and Mrnamentioning
confidence: 99%
See 3 more Smart Citations